The Antiproliferative Activity and NO Inhibition of Neo-Clerodane Diterpenoids from Salvia guevarae in RAW 264.7 Macrophages - Juan Pablo Torres-Médicis; Celia Bustos-Brito; Leovigildo Quijano; Brenda Y. Bedolla-García; Sergio Zamudio; Teresa Ramírez-Apan; Diego Martínez-Otero; Baldomero Esquivel (Molecules)
In this study, nine neo-clerodane-type diterpenoids (1–9) were isolated from the dichloromethane extract of Salvia guevarae Bedolla & Zamudio leaves. Compounds 1–6 were new natural products, and 7–9 were acetone artifacts. In addition, four neo-clerodanes diterpenoids (10–13) previously described from different sources and six triterpenoids—identified as 3β,20,25-trihydroxylupane, oleanolic acid, 3β-O-acetyl-oleanolic acid, ursolic acid, 3β-O-acetyl-betulinic acid, and 3β,28-O-diacetyl-betulin—were isolated. Additionally, five flavonoids were also isolated from the methanol extract: quercetin-3-O-β-xylopyranosyl-(1 → 2)-β-galactopyranoside, taxifolin-7-O-β-glucopyranoside, naringenin-7-O-β-glucopyranoside, a mixture of 2R and 2S eriodictyol-7-O-β-glucopyranoside, caffeic acid, the methyl ester of rosmarinic acid, and rosmarinic acid. The structure of the isolated compounds was established by spectroscopic means, mainly 1H and 13C NMR, including 1D and 2D homo- and heteronuclear experiments. The absolute configuration of 1 and 10 was ascertained via an X-ray analysis, and that of the other compounds via ECD. The antiproliferative activity of some diterpenoids was determined using the sulforhodamine B method, where guevarain B (2) and 6α-hydroxy-patagonol acetonide (7) showed moderate activity against the K562 line, with IC50 (μM) = 33.1 ± 1.3 and 39.8 ± 1.5, respectively. The NO inhibition in RAW 264.7 macrophage activity was also determined for some compounds, where 2-oxo-patagonal (6), 6α-hydroxy-patagonol acetonide (7), and 7α-acetoxy-ent-clerodan-3,13-dien-18,19:16,15-diolide (10) were proven to be active, with IC50 (μM) of 26.4 ± 0.4, 17.3 ± 0.5, and 13.7 ± 2.0, respectively. The chemotaxonomy of Salvia guevarae is also discussed.